IMPROVING VOCABULARY MASTERY USING INTERACTIVE MIND MAPPING METHOD TO THE SEVENTH GRADE OF SMP N 32 SEMARANG - Dwi Handayani; Fitri Yulianti; T Sri Suwarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based an a study which attempts to examine the use of the mind mapping method in improving vocabulary for 7th grade students of SMP N 32 Semarang. The purpose of this research was to find out the mind mapping method in improving students vocabulary. The objectives of this study are (1) To find out the students’ vocabulary achievement before using the interactive mind mapping method, (2) To find out the students’ vocabulary achievement after using the interactive mind mapping method, (3) To find out whether there is an improve student’s English vocabulary through interactive mind mapping method achievement significantly. (4) To find out the students’ perception of the use mind mapping to improve their vocabulary. Pre-experimental research was used in this study method. In this study, the researcher collects the data by using the tests and questionnaire. The researcher uses the statistical calculation with SPSS in data analyzed. The sample of this research is one class from 7th. The class has 31 students. As a results , it can be witnessed from the mean of pre-test and post-test. In pre-test result is 81,4. After being given treatment,the post-result is 86,9. Moreover, the hypothesis result showed that Ha is accepted. Because, T-count was higher than T-table (2.846 > 1.710), it indicates that there was a significantly improving vocabulary using mind mapping method.